Effective adsorption of heavy metal ions in water by sulfhydryl modified nano titanium dioxide - Chen, Beibei; Li, Lin; Liu, Lei; Cao, Jianxin (Frontiers in Chemistry, 2023)
Background: The monitoring and removal of heavy metal ions in wastewater will effectively improve the quality of water and promote the green and sustainable development of ecological environment. Using more efficient adsorption materials and more accurate detection means to treat heavy metal ions in water has always been a research focus and target of researchers. Method: A novel titania nanomaterial was modified with sulfhydryl group (nano TiO2-SH) for detection and adsorption of heavy metal ions in water, and accurately characterize the adsorption process using Surface-Enhanced Raman Spectroscopy (SERS) and other effective testing methods. Results: The maximum adsorption efficiency of nano TiO2-SH for the Hg2+, Cd2+, Pb2+ three heavy metal ions reached 98.3%, 98.4% and 98.4% respectively. And more importantly, after five cycles of adsorption and desorption, the adsorption efficiency of nano TiO2-SH for these three metal ions is still above 96%. Conclusion: These results proved the nano TiO2-SH adsorbent has great potential in practical water pollution purification.